Privatization or Public Private Partnerships? The State's Role in Education (International Journal of Innovative Research in Engineering & Management, 2023)
This article examines the Indian  government's projected public–private partnership (PPP)  efforts in educational in its Eleventh and Eleven Five Year  Plans. The research seeks to establish the state's role as a  financier, manager, and administrator of instruction using  the recommended PPP approaches. The findings show that  PPPs in schools are directly linked to privatized, or that,  despite assertions of a "vastly increased role that the  nation," the recommended techniques limit the state's  participation in education financing, administration, and  governance. In compare to most African and Latin  American countries' experiences, there has been little  focus in the broader policy debate on the role that  reinvigorated marketing of a domestic manufacturing  capacity in either an import tariffs atmosphere out over  five decades that followed liberation may well have rarely  played in nurturing specific prerequisites that enabled  globalization but instead nationalization policy positions  to 'take' as much favorably.
Keywords: Education; Governance and Public Policy; Education in South Asia; PPP; Social Sector